Bronchial balloon occlusion in children with complex pulmonary air leaks. Issue 2 (6th December 2012) - Hathorn, Claire; Armitage, Nicole; Wensley, David; Seear, Michael
Abstract : Pulmonary air leaks in children are most commonly due to infection or barotrauma. While cases of severe barotrauma are falling because of advances in neonatal care, the incidence of necrotising pneumonia is rising. The majority of air leaks can be managed conservatively, but more severe cases pose a significant challenge to the clinician. The use of occlusive endobronchial balloons is an established anaesthetic technique for a number of indications, but is not widely used in children. We conducted a review over a 12-year period, and report six cases of complex air leaks in which balloon occlusion was used. Balloon occlusion was successful in both cases of bronchopleural fistulae (secondary to severe necrotising pneumonia) and half of the cases of intrapulmonary air leak (due to barotrauma). In the other two cases (due to barotrauma and filamin A deficiency), it was transiently effective. No serious adverse effects or complications were encountered. In selected cases, endobronchial balloons are a useful adjunct in the management of life-threatening bronchopleural fistulae and cystic lung disease. The procedure is non-operative, minimally invasive and reversible. With the increasing incidence of bronchopleural fistulae, this may become an increasingly important therapy.